2021
DOI: 10.1155/2021/5565434
|View full text |Cite
|
Sign up to set email alerts
|

Election Prediction on Twitter: A Systematic Mapping Study

Abstract: Context. Social media platforms such as Facebook and Twitter carry a big load of people’s opinions about politics and leaders, which makes them a good source of information for researchers to exploit different tasks that include election predictions. Objective. Identify, categorize, and present a comprehensive overview of the approaches, techniques, and tools used in election predictions on Twitter. Method. Conducted a systematic mapping study (SMS) on election predictions on Twitter and provided empirical evi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…It also identified challenges associated with sentiment analysis for election predictions including the activities of bot accounts, changing moods and opinions of voters, tweets with names of more than one entity making the sentiment analysis trickier, and the unavailability of a training dataset. Another work by Khan et al [23] undertook to systematically map election predictions on Twitter and comprehensively reviewed the tools, techniques and approaches utilized for election prediction on Twitter with 98 studies between 2010 and 2021. The findings showed that although elections result of 28 countries were analyzed and predicted, the elections of the United States of America (USA) and that of India formed the bulk of the election prediction analysis constituting more than 50% of the predictions.…”
Section: Review Of Related Workmentioning
confidence: 99%
“…It also identified challenges associated with sentiment analysis for election predictions including the activities of bot accounts, changing moods and opinions of voters, tweets with names of more than one entity making the sentiment analysis trickier, and the unavailability of a training dataset. Another work by Khan et al [23] undertook to systematically map election predictions on Twitter and comprehensively reviewed the tools, techniques and approaches utilized for election prediction on Twitter with 98 studies between 2010 and 2021. The findings showed that although elections result of 28 countries were analyzed and predicted, the elections of the United States of America (USA) and that of India formed the bulk of the election prediction analysis constituting more than 50% of the predictions.…”
Section: Review Of Related Workmentioning
confidence: 99%
“…Twitter data has been used to study a wide range of topics, including troll activity [18], cognitive reflection [19], digital trace data to study migration and migrants [20], expressed sentiment alterations during the COVID-19 pandemic [21,22], misinformation spread during earthquakes [23], and spatial analysis of gunshots reports [24]. In the context of politics, there has been focus on the influence of fake news [7,25], campaigning [8,9,26], echo chambers [27], polling [28], and elections [29]. For online polling and election predictions the preferred methods of analysis are based either on sentiment [6], volume [5], or social networks [28], and hybrid methods are the exception rather than the rule [29].…”
Section: Introductionmentioning
confidence: 99%
“…24 Still, it is a highly interesting forum of ideas exchange, reflecting the opinion pulse check in many ways: Twitter discourse analysis is useful in understanding different social phenomena. [25][26][27] It can be even used as a useful election prediction tool 28 or new venture success. 29…”
Section: Introductionmentioning
confidence: 99%